Urban and Buildings Regeneration Strategy to Climatic Change Mitigation, Energy, and Social Poverty after a World Health and Economic Global Crisis - Mercader-Moyano, Pilar (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In recent months, we have suffered the effects of an unexpected global health crisis that has led to an even worse global economic crisis, with GDPs plummeting to unprecedented levels. While our health workers struggle to find a vaccine to protect our health, we have had to live through situations hitherto unimagined, and we have spent even more time in our homes while our streets remained empty, which has brought to light the weaknesses and strengths of our system and our way of building and designing. Our aim is to publish research projects and papers that contribute to reactivate the Construction Sector from within, in the context of this world economic crisis. Such an effort will focus especially on solutions that improve the quality of indoor air in buildings, strengthening the circular economy in an eco-efficient rehabilitation of buildings and neighborhoods in our cities.